Unlocking the Potential of Second Grade Students : Emotional Quotient as a Catalyst for Early Reading Skills Development - Salam, Rosdiah; Rukayah, Rukayah; Rolinsa, Yusuf Denilson; Idrus, Nur Abidah; Faisal, Muhammad (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the Emotional Quotient level, reading achievement level, and emotional quotient’s effect on reading achievement in grade II students. This method of research was ex-post facto with a quantitative approach. The instrument used to measure students’ emotional quotient levels was a questionnaire; meanwhile, the instrument used to measure students’ reading achievement levels was documentation. Furthermore, the data analysis technique was descriptive analysis, then proceeded with the prerequisite analysis test, starting from the normality and linearity tests. Finally, the research hypothesis was tested using a simple linear regression test and the F test. The result was that most students have a relatively low EQ, so their reading achievement was relatively low too. The results of a straightforward regression analysis yield the equation Y = 45.788 + 0.406X, which showed that an increase in the reading performance score of 0.406 would occur for every additional unit of emotional quotient score. Thus, a significant positive relationship existed between kids’ EQ and reading achievement. Self-awareness, mood management, self-motivation, empathy, and relationship management were essential considerations when increasing students’ emotional quotient (EQ). While age, teaching strategies, the environment in which students learn, and parental and educational support for encouraging and assisting students in learning to read were among the elements that influence students’ reading achievement.